(untitled) (Journal of actual problems of jurisprudence, 2019)
In given article the author reveals the history of a state administration and regulation of forest fund of Republic of Kazakhstan . As by the author on the basis of the analysis of actions of the legislation and state administration system forest fund it is given some recommendations about perfection of the forest legislation.